An Analysis Of Factors Affecting The Decision To Use The Quick Response Code Indonesian Standard (Qris) As A Digital Payment System - Hasan Abdullah; Ahmad Soleh; Aji Sudarsono (Utami Publisher, 2026)
This study aims to analyze the influence of the Technology Acceptance Model (TAM), Trust, Promotion, Cost, and Facility Conditions on the Decision to Use QRIS in Bengkulu City, both partially and simultaneously. This study uses a quantitative approach with a survey method, involving a sample of 100 QRIS users in Bengkulu City selected through purposive sampling. Primary data were collected using an online questionnaire and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method with SmartPLS 4 software. The results show that TAM, Cost, and Facility Conditions partially have a positive and significant effect on the Decision to Use QRIS. Conversely, Trust and Promotion were found to have no significant effect partially. Simultaneously, the five independent variables of TAM, Trust, Promotion, Cost, and Facility Conditions were proven to have a significant effect on the Decision to Use QRIS, with R2 value of 0.583, which means that these variables were able to explain 58.3% of the variation in the Decision to Use QRIS.